Analysis of working hours of married women in Bali Province - Ni Putu Ayu Sumariani (Privietlab, 2025)
Based on data from the Bali Province Central Statistics Agency, female labor force participation continues to increase over time. Married women experience the dual burden of managing domestic responsibilities and employment outside the home. The expansion of job opportunities and the rise in real wages are among the factors that drive the increased labor supply of married women. The labor supply is closely tied to wage levels. This study aimed to analyze the number of working hours of married women in Bali Province and identify the factors that influence it. The study used primary data collected from 100 respondents through a structured questionnaire. The analysis was conducted using the ordinary least squares (OLS) method, with independent variables including the wages of married female workers, husband's income, and household expenditures. The dependent variable was the number of hours worked by married women. The results show that wages and household expenditures have a positive and significant effect on working hours, while husband's income does not have a significant influence. This indicates that economic demand and household needs are key drivers for women to participate more actively in the labor market, despite their domestic responsibilities.